Analysis of SDGS research: The relationship between climate change, poverty, inequality, and food security: The Indonesian context - Wiharta Dewananda; Driana Leniwati; Agung Prasetyo Nugroho Wicaksono (Universitas Muhammadiyah Yogyakarta, Indonesia, 2023)
Research aims: This study investigates the linkages between climate change, inequality, and food security. The study attempts to provide an understanding of the evolution of publications on the topic to identify key emerging themes and policy prescriptions.Design/Methodology/Approach: Mixed methods, bibliometric analysis, and content analysis were employed to examine emerging themes in the literature on climate change, inequality and poverty, and food insecurity in Indonesia. The bibliometric data used were taken from the Gscholar database for 2018-2023.Research findings: The study generated six research themes based on the analyzed literature: (1) Human resource management and wealth redistribution through zakat; (2) Agricultural adaptation to climate change and the concept of sustainable agriculture; (3) Policies or rules applied by the government to regulate the agricultural sector; (4) Limited access to resources, loss of employment, and income in food insecurity among households; (5) Poverty alleviation strategies in reducing inequality and improving the quality of human life; and (6) Comprehensive and sustainable planning to identify challenges, opportunities, policies, inclusive economy, and food security.Theoretical contribution/Originality: This study analyzes and uncovers emerging topics in the field and their contributions to the literature, as well as persistent gaps, and provides future research directions based on emerging themes and policy prescriptions.Practitioner/Policy implication: This study can be used by the government as a regulator and financial institutions as a means of financing and academics.Research limitation/Implication: Future research is expected to examine: (1) The planning of government agencies in mobilizing local resources; (2) The role of zakat institutions in poverty alleviation programs; (3) Sustainable agriculture models; (4) CWLS Green Sukuk financing models; (5) The role of microfinance institutions in poverty alleviation programs; and (6) Studies on cultural economy.